2020
DOI: 10.1017/9781108278287
|View full text |Cite
|
Sign up to set email alerts
|

The Making of the Indo-Islamic World

Abstract: In a new accessible narrative, Andre Wink presents his major reinterpretation of the long-term history of India and the Indian Ocean region from the perspective of world history and geography. Situating the history of the Indianized territories of South Asia and Southeast Asia within the wider history of the Islamic world, he argues that the long-term development and transformation of Indo-Islamic history is best understood as the outcome of a major shift in the relationship between the sedentary peasant socie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…Instead, as Chaudhuri (1971) argued, the territory represented by India in the pre-modern era might better be seen as divided between three concentric circuits of trade and civilization connecting parts of its society to parts elsewhere across the Indian Ocean, including the Gulf region. Along similar lines, Wink (1991) defined a space called "Indo-Islamic world," which included parts of South Asia and the Middle East and demonstrated that Islam acted as a glue that held this "worldsystem" together. These exchanges point toward the permeability of what are often assumed to be closed national borders and "cultural zones" (Subrahmanyam, 1997).…”
Section: From Transnationalism To Transregionalismmentioning
confidence: 99%
“…Instead, as Chaudhuri (1971) argued, the territory represented by India in the pre-modern era might better be seen as divided between three concentric circuits of trade and civilization connecting parts of its society to parts elsewhere across the Indian Ocean, including the Gulf region. Along similar lines, Wink (1991) defined a space called "Indo-Islamic world," which included parts of South Asia and the Middle East and demonstrated that Islam acted as a glue that held this "worldsystem" together. These exchanges point toward the permeability of what are often assumed to be closed national borders and "cultural zones" (Subrahmanyam, 1997).…”
Section: From Transnationalism To Transregionalismmentioning
confidence: 99%
“…Historical accounts between the ninth and 15 th centuries are sparse and unfortunately do not describe the nature of interactions of foreign peoples. For instance, Wink (1990) observed that Jiroft, in present day Iran ‘became ‘the residence of the foreigners of India and Byzantium’ in the early 12 th century (p. 59). Even so, a stronger commercial colony of Hindu merchants developed in Muscat, Oman in the 15th century and gradually spread to other parts of the Arab Peninsula (Claude, 2000, p. 10–11).…”
Section: The History Languages In the United Arab Emiratesmentioning
confidence: 99%
“…From the Indian side, right from the early medieval times, Multan served as the centre for the trade with Islamic regions. Arab geographers of the period have described the city as a large and prosperous where 9 caravans from Khurasan used to come regularly. Kabul, another important centre for the trade, was frequently visited by merchants who purchased Indian dried fruits and kernels, used in the making of medicines.…”
Section: Introductionmentioning
confidence: 99%